ANALYSIS OF INTERACTIVE DIGITAL MEDIA NEEDS BASED ON LOCAL WISDOM FOR STRENGTHENING CULTURAL LITERACY IN ELEMENTARY SCHOOL IPAS LEARNING - Fitrotis Sa’adah; Maretha Dellarosa; Fiena Saadatul Ummah (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
The rapid development of digital technology and changes in elementary students' learning characteristics demand contextual and meaningful learning experiences, including the strengthening of cultural literacy. Integrated Natural and Social Sciences (IPAS) learning has strategic potential to connect natural, social, and cultural concepts; however, classroom practices in elementary schools still show limited use of digital learning media that incorporate local cultural contexts. This study aims to analyze the needs for developing interactive digital media based on local wisdom to strengthen cultural literacy in elementary IPAS learning. A qualitative descriptive approach with a needs analysis design was employed. Data were collected through semi-structured interviews with teachers, limited classroom observations, and document analysis. The data were analyzed qualitatively through data reduction, data display, and conclusion drawing. The findings indicate that IPAS learning is still dominated by general learning resources that are not yet integrated with local cultural contexts. Teachers require interactive digital media that are easy to use, aligned with students' characteristics, and capable of connecting IPAS content with local wisdom. The local cultural potential of Gresik is highly relevant to be utilized as a learning context in IPAS instruction. Based on these findings, the BESTARI interactive digital media is positioned as a conceptual solution that can be further developed to support cultural literacy strengthening in elementary IPAS learning.